A curious case of enterocutaneous fistula in incisional hernia secondary to broken tip of Ryles tube - Settipalli, Saisree; Kamat, Manmohan M.; Joshi, Amol; Mishra, Avani; Suralkar, Shyam; Parmar , Sakshi (International Surgery Journal, 2023)
Enterocutaneous fistula is an abnormal connection that develops between the intestinal tract and the skin with drainage of intestinal contents through the skin. Enterocutaneous fistulas secondary to intraluminal foreign body are relatively rare. We report a case of 75-year-old bedridden female on Ryles tube feeding presented with painful swelling over mild line scar of abdomen and skin opening with watery discharge from lower end of scar. Radiological imaging revealed an obstructed incisional hernia with enterocutaneous fistula likely communicating to ileum. Intra-operatively an unexpected broken tip of Ryles tube was delivered through fistula opening. Patient managed successfully with fistula excision, wedge resection and closure. This case highlights the need for adaptability and timely action during surgical intervention.